A property-based genetic algorithm for order acceptance and scheduling with common due window. Issue 10 (2022) - Zhao, Ziye; Chen, Xiaohui; An, Youjun; Li, Yinghe
Abstract: In a competitive make-to-order production environment, limited production capacity and strict delivery requirement prompt the manufacturer to make decisions of order acceptance and scheduling simultaneously with maximization of the total net profit (TNP). In this context, this paper studies an order acceptance and scheduling (OAS) problem in a single machine environment, and the earliness/tardiness penalties are exsiting when an order is not delivered on time under the common due window. To solve this problem, the membership function of earliness/tardiness penalties is designed and a mathematical model for maximizing the TNP is established. According to the characteristics of the problem, three properties that are related to rejecting orders, sequencing orders and determining the starting time of orders are derived separately. Based on these, a property-based genetic algorithm (P-GA) is designed to search for the optimal solution. In numerical experiments, the effectiveness and superiority of the proposed P-GA are demonstrated by comparing with the solutions that are obtained by other two heuristic algorithms.